False-Positive and False-Negative Misclassification of Liver Scans - Barnett, V. (Methods of Information in Medicine, 1978)
Liver scans are used in the study of hepatic cancer. Changes in the size of perfusion defects may prompt the judgment of progression or regression of the disease. Assessments of change of size are usually made subjectively and there is the possibility that different investigators may differ in their assessments of a perfusion defect or that a particular investigator may not be consistent in his assessment from one time to another. Various possibilities of misclassification exist. A defect which is unchanged may be adjudged to have progressed or regressed (false-positive misclassification); true progression (or regression) may fail to be discerned (false-negative misclassification).An experiment was conducted to examine the assessment of perfusion defect areas by a group of experienced oncologists examining a set of liver scans. Misclassification probabilities were estimated and their extent gives grounds for concern. False attribution of progression (or regression) at the 50% level occurs with probabilities in the range 0.23 to 0.37. Failure to adjudge progression (regression) at the 50% level, where there is true progression at the 100% level, arises with an estimated probability in the range 0.20 to 0.26. The higher values refer to cases where different investigators examine the scans on two occasions; the lower values when one investigator makes both assessments. Unjustified rounding-off of measured values seems an important factor in the occurrence of misclassification.
Keywords: Liver Scans; Hepatic Cancer; Areas of Perfusion Defect; Measurement Errors; Incorrect Attribution of Progression or Regression